Preparation and Photocatalytic Characterization of Modified Nano TiO2/Nd/Rice Husk Ash Material for Rifampicin Removal in Aqueous Solution - Thuy Dang Thi Ngoc; Ha Nguyen Thi; Dung Nguyen Duc; Sen Nguyen Thi; Toan Nguyen Duc; Nam Nguyen Hoang (Journal of Analytical Methods in Chemistry)
Antibiotics like rifampicin are often persistent in the environment. When entering the water, it causes antimicrobial resistance that affects the ecosystem and accumulates in the aquatic organisms and affects human health through the food chain. In this study, titanium dioxide was doped with neodymium (0.01 to 0.8%) using the sol-gel hydrothermal method. TiO2/Nd was then coated on rice husk ash to produce a modified TiO2/Nd/rice husk ash material containing 0.36% (w/w) Nd. The structural characteristics and photocatalytic properties of the materials were analyzed by X-ray diffraction, energy dispersive X-ray, transmission electron microscopy, scanning electron microscopy, forbidden zone energy, and specific surface area. The TiO2/Nd material exhibited a higher photocatalytic decomposition capacity than TiO2 and depended on the Nd content. The rifampicin removal efficiency of TiO2/Nd materials with 0.36 to 0.80% Nd contents was approximately 40% higher than that of TiO2/Nd containing 0.01 to 0.28% Nd. A new photocatalytic TiO2/Nd/rice husk ash material was developed to decompose rifampicin. The rifampicin-degrading efficiency of TiO2/Nd and TiO2/Nd/rice husk ash material reached approximately 86 and 75%, respectively, within 90 min under sunlight. Although a lower efficiency was obtained, the TiO2/Nd/rice husk ash material was selected to degrade rifampicin residue in water via the photocatalytic process (under sunlight) because of its advantages such as requirement of a small amount and easy recovery. In the rifampicin removal process, k values were found to match the zero- and first-order kinetics. In particular, for TiO2/Nd and TiO2/Nd/rice husk ash under solar irradiation, R2 values reached approximately 0.98. These results have been previously published as a preprint.